S124 Cardioprotective medication in Duchenne muscular dystrophy: a single-centre cohort study. (11th November 2022) - Kisel, J; Ballard, E; Suh, E; Hart, N; Kapetanakis, S; Srivastava, S; Marino, P; Murphy, P; Steier, J
Abstract : Introduction and Objectives: Duchenne's muscular dystrophy (DMD) is a neuromuscular disorder characterised by progressive muscle wasting impacting mobility, ventilation and cardiac function. Home mechanical ventilation (HMV) has led to improved respiratory outcomes, while the associated neuromuscular cardiomyopathy remains a major cause of morbidity and mortality. We investigated the effects of cardioprotective medications (ACE-inhibitors, ACE-I, and beta-blockers) on clinical outcomes in patients with DMD. Methods: This was a retrospective cohort study (reference:2021/12469) of DMD patients at a tertiary referral centre analysing service data between 1993–2001 and screening the electronic patient records for demographics, comorbidities, medication, disease specific features, echocardiography, hospitalisations, and ventilator use. Data were reported as mean (standard deviation) if normally distributed. The level of significance was defined as p<0.05. Results: 68 patients were identified aged 27.4(6.6) years, of which 52 were still alive. There was a reduced body mass index in survivors compared to deceased patients (23.8(5.9) vs 19.9(3.8)kg/m 2 ; p=0.03). HMV was required for hypercapnic respiratory failure in 89.7% of the patients after a follow up period of 94 (79) months. There were no differences in ventilator settings between the survivors and deceased patients. 85% of the cohort had DMD associated cardiomyopathy. About 2/3 of all hospitalisations during the observation period were secondary to cardiopulmonary causes. At the time of the review, all patients were non-ambulatory, 69% used a mechanical insufflator:exsufflator device (MIE), 45% had feeding tubes (PEG), and 40% had spinal surgery. The left ventricular ejection fraction (LVEF) at initial presentation was 44.8(10.6)% and declined by -3.3(95% Confidence Interval (CI) 0.4 to -7)% over the follow up period (p=0.002). 61 patients were established on ACE-I for 75.9(35.1)% of the time, and 62 were on beta-blockers for 73.6(33.5)% of the follow up period. There was a significant decline in the LVEF in those who took ACE-I for limited periods only compared to those who remained permanently on ACE-I (p=0.002); a similar effect was recorded with beta-blockers (p=0.02). Conclusion: Continuous long-term use of ACE-I and beta-blockers is associated with a reduced decline in LVEF in patients with DMD and may be protective of adverse cardiovascular ill health.